Combatting IUU Fishing in Ghana - Wiafe, G. (My University, 2016)
Globally, Illegal, Unregulated and Unreported (IUU) fishing has created large declines in commercially important fish populations and is thus recognized as a major threat, with the potential to cause an irreversible change in marine ecosystems. It has been estimated that IUU fishing accounts for about 20% of world catches, representing a global loss of between US$10 billion and US$23.5 billion annually. In West Africa alone, IUU fishing costs the region $7.15b, equivalent of 2.9m tons of illegally harvested fish. Such losses are detrimental to socio-economic development of the region, where over 3 million people, directly or indirectly are employed by the fisheries sector; per capita consumption of fish as animal protein exceeds global average; and up to 30% of GDP in some countries comes from fishery export revenues. The difficulty in combatting IUU fishing stems from inadequate human and infrastructural capacity to enforce fishery regulation, problem of internal conflict and political strife, and priorities other than fishery management requiring governmental attention. It goes without saying that dependence on foreign aid to balance national budget has also encouraged legal fishing fleets to overfish the resource in the region. Furthermore, inability to police the extent of the EEZ makes it possible for large factory ships from industrialized countries, stationed within the high seas, to carry out indiscriminate poaching. Notwithstanding these challenges, the ECOWAS Commission and its two Sub-Regional Fisheries Bodies, have put in place some measures to address IUU fishing in the region. The interventions include harmonization of fisheries legislation, setting up of national fishing registers, deployment of vessel monitoring systems (VMS), and cross-border patrols. The use of Earth Observation (EO) data coupled with technological advancement is playing a key role in maritime sensing in many developed countries. Hence, the ECOWAS Commission has set up a Regional Marine Centre in the University of Ghana as part of the Monitoring for Environment and Security in Africa initiative. The focus is to utilize EO data and innovative technologies for environment and resource management. This presentation will showcase how the Centre is helping to fight IUU fishing among others. Fourteen countries, from Mauritania to Sao Tome e Principe, receive daily intelligence on activities of all manner of vessels within their exclusive economic zones. Through a collaboration with exactEarth of Canada, a pilot programme to monitor inshore vessels in Ghana has resulted in deployment of transponders on all inshore fishing vessels in Ghana by the Ministry of Fisheries and Aquaculture Development. The results from the one-year pilot will be presented in the context of fighting IUU fishing.
Seminar
Keywords: Illegal, Unregulated and Unreported (IUU); fish populations; socio-economic development; fisheries sector